Subjective vs Objective Evaluation of Knee Stability in Patients before and after Anterior Cruciate Ligament Reconstruction - Joanna Ficek; Krzysztof Ficek; Grzegorz Juras; Dawid Pawlak; Aleksandra Wysota (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
Every year, the number of anterior cruciate ligament ruptures increases considerably. The present analysis compares patients’ subjective sensations after the ACL injury to an objective arthrometric examination. The subjective evaluation of the knee-joint condition was performed using the Lysholm score scale and IKDC 2000 scale, whereas the objective evaluation was performed using a GNRB device to obtain an arthrometric measurement. Both measurement methods were performed before ACL reconstruction and after the rehabilitation process of ±11.5 months. The following research was conducted on a group of 8 patients who underwent anterior cruciate ligament reconstruction. Statistical analysis did not reveal any significant differences between the arthrometric examination and the subjective score scales. The test indicated the significant differences between the score scales questionnaires completed before and after the surgery. The conclusions that can be drawn from the present analysis show us the importance of using subjective evaluation devices. Despite the lack of significance in the examination performed with the objective device, the self-evaluation of knee-joint efficiency made by the patient indicated a significant improvement.